Lion [videorecording (Blu-Ray)] - Davies, Luke, 1962-; Patel, Dev, 1990-; Pawar, Sunny; Wenham, David, 1965-; Kidman, Nicole, 1967-; Mara, Rooney; Bharate, Abhishek; Ladwa, Divian; Bose, Priyanka; Dīptī Navala; Chatterjee, Tannishtha; Siddiqui, Nawazuddin; et al. (Anchor Bay Entertainment, 2017)
Five-year-old Saroo gets lost on a train which takes him thousands of kilometers across India, away from home and family. Saroo must learn to survive alone in Kolkata, before ultimately being adopted by an Australian couple. Twenty-five years later, armed with only a handful of memories, his unwavering determination, and a revolutionary technology known as Google Earth, he sets out to find his lost family and finally return to his first home.